Analisis Determinan Promosi Jabatan pada Perum Perhutani Kesatuan Pemangku Hutan (KPH) di Pekalongan Barat - Ratna Pujiastuti; Harsuti Harsuti; Ady Achadi; Dina Marina (FEB UNWIKU PURWOKERTO, 2022)
This study examines the determinants of promotions carried out at the Perum Perhutani Forest Stakeholder Unit (KPH) Pekalongan Barat. Factors studied include competence, seniority and loyalty. The sampling method used the Slovin formula with the number of respondents as many as 187 people. The analytical tool used in this study is multiple linear regression with the help of SPSS version 23. The results showed that competence had a positive and significant effect on it. seniority has a positive and significant effect rejected. loyalty has a positive and significant effect accepted. The implication of this research is that the leader of the West Pekalongan KPH should pay attention to competence and loyalty when doing promotions. The way to improve competence is to give employees the opportunity to take part in training that can improve work abilities so that employees can complete their duties properly. To increase loyalty, the leadership of KPH Pekalongan Barat must establish communication between employees so that they have good relations and conduct socialization of policies or regulations so that employees can obey them properly. Further researchers should use other variables other than seniority, because based on the results of the research, the seniority variable does not have a significant effect on promotion.